THE COMPARATIVE ANALYSIS AND POPULARITY OF USAGES OF BOTH ACCENTS AND DIALECTS, INCLUDING VARIABILITIES OF APPLIANCES OF ENGLISH LANGUAGE ON THE EXAMPLES OF LATIN AMERICAN COUNTRIES SUCH AS PERU, CHILE REPUBLIC, ARGENTINA AND BRAZIL (THE SCIENTIFIC ARTICL (Pedagogical Cluster-Journal of Pedagogical Developments, 2026)
Nowadays the number of English speakers in Latin American countries is growing exponentially, in other words a great number of people in Latin American countries started to learn English as the first or the second language primarily in schools. English language is gaining a wide popularity between different layers of society ranging from simple workers so called blue collar workers up to the middle class, and, definitely mentioning the upper layers of society.